Haram Manyarah Waja Sampai Kaputing: Tazkiyatun Nafs dalam Masyarakat Dayak - Maulana, Muhammad; Jamalie, Zulfa; Wibowo, Fasih; Sani, Abdul (Fahima, 2024)
Haram Manyarah Waja Sampai Kaputing character education is character education based on the values of local wisdom of the Dayak Community of South Kalimantan Province, this is the principle of Prince Antasari who is one of the national heroes who is very firm and brave. Prince Antasari’s Azam is hope for the Dayak people to continue fighting without giving up, and this is related to Tazkiyatun Nafs. This research discusses the meeting point between Azam Prince Antasari as the life motto of the Dayak community “Haram Manyarah Waja Sampai Kaputing” and Tazkiyatun Nafs in character education. With this study, Haram Manyarah Waja Sampai Kaputing can be more easily understood practically from the perspective of Tazkiyatun Nafs on character education by the younger generation. This research approach includes a theological approach which aims to study through religious reasoning. The theological approach is intended to look at the concept of Haram Manyarah Waja Sampai Kaputing in the context of Tazkiyatun Nafs. The theological approach is intended to explore the condition of character education in the Dayak community by contextualizing it. This research uses a descriptive analytic analysis method, which aims to describe or provide an overview of the basic suitability of Haram Manyarah Waja Sampai Kaputing with Tazkiyatun Nafs.